IMPLEMENTASI DIGITALISASI E-WALLET (KOPI-KOE) SEBAGAI SALAH SATU PRODUK LAYANAN KEUANGAN DI PT BPR BKK TEMANGGUNG (PERSERODA) KANTOR CABANG NGADIREJO - Nandini, Amanda Precillia Tiara; Manurung, Herlina (Mount Hope Management International Journal, 2025)
People's Credit Bank (BPR) is defined by Law No. 10 of 1998 Article 1 concerning Banking as follows: "People's Credit Bank is a Bank that carries out its business activities conventionally or based on sharia principles which in its activities do not provide services in payment traffic". The rapid development of digital technology requires BPR BKK Temanggung to make new innovations, one of which is the use of E-wallets. One of the digital financial service products produced by this partner agency is the application (Kopi-Koe). The purpose of this study is to find out how BPR BKK Temanggung implements digital applications. The type of research used in this report is qualitative methods. The result of this study is the impact of the implementation of digital applications (Kopi-koe), among others, providing convenience for customers, streamlining time and operations, and increasing the growth of BPR BKK Temanggung's Financial Performance.